From hunters to herders. Reflections on the “Ecological Migration” of the Chinese Evenki reindeer herders - Xie, Yuanyuan (Études mongoles et sibériennes, centrasiatiques et tibétaines, 2018)
The “traditional way of life” among the Evenki reindeer herders of China has faced many changes after their “Ecological Migration” in 2003 and the hunting ban. Evenki identity has thus shifted, as they are officially categorised as “reindeer herders” rather than “hunters”. Being identified as a “hunter” meant access to welfare within the government’s institutional arrangement. Furthermore, since 2009, the local government has reconsidered its stance towards the traditional lifestyle of the Evenki and has striven to foster tourism. Based on fieldwork conducted in 2003-2004 and during several visits from 2011 to 2014, this paper first examines various governmental policies aimed at the Evenki. It then analyses the present situation of the Evenki, in particular examining resource conflicts and changing identities. Le « mode de vie traditionnel » des Évenks éleveurs de rennes de Chine a connu d’importants changements suite à la « migration écologique » de 2003 et l’interdiction de la chasse. Ainsi, l’identité des Évenks est passée du statut de « chasseurs » à celui d’« éleveurs de rennes ». Dans le passé, la désignation de chasseurs ne renvoyait pas seulement à une identité ethnique, mais également à une identité politique. Par ailleurs, depuis 2009, le gouvernement local tente de revaloriser le mode de vie des Évenks éleveurs de rennes en développant le tourisme. Basé sur une enquête de terrain d’une année menée en 2003-2004 et sur plusieurs visites effectuées entre 2011 et 2014, cet article examine dans un premier temps les diverses politiques gouvernementales conduites chez les Évenks éleveurs de rennes. Il analyse ensuite la situation actuelle des Évenks, les conflits liés aux ressources et les changements d’identités.